The Problems of Implementing the ePrivacy Directive and Their Solutions in ePrivacy Regulation - Markevičius, Edgaras (Teisė, 2019)
This article attempts to describe the most significant practical problems in implementing the ePrivacy Directive and analyzes whether the legal preconditions for their solution are present in the draft of ePrivacy Regulation.